# How do you solve (-4h-(-5))/(-7)=13?

Oct 5, 2017

See a solution process below:

#### Explanation:

First, rewrite the numerator of the fraction on the left side of the equation. Remember, minus a minus is a plus:

$\frac{- 4 h + 5}{-} 7 = 13$

Next, multiply each side of the equation by $\textcolor{red}{- 7}$ to eliminate the fraction while keeping the equation balanced:

$\textcolor{red}{- 7} \times \frac{- 4 h + 5}{-} 7 = \textcolor{red}{- 7} \times 13$

$\cancel{\textcolor{red}{- 7}} \times \frac{- 4 h + 5}{\textcolor{red}{\cancel{\textcolor{b l a c k}{- 7}}}} = - 91$

$- 4 h + 5 = - 91$

Then, subtract $\textcolor{red}{5}$ from each side of the equation to isolate the $h$ term while keeping the equation balanced:

$- 4 h + 5 - \textcolor{red}{5} = - 91 - \textcolor{red}{5}$

$- 4 h + 0 = - 96$

$- 4 h = - 96$

Now, divide each side of the equation by $\textcolor{red}{- 4}$ to solve for $h$ while keeping the equation balanced:

$\frac{- 4 h}{\textcolor{red}{- 4}} = \frac{- 96}{\textcolor{red}{- 4}}$

$\frac{\textcolor{red}{\cancel{\textcolor{b l a c k}{- 4}}} h}{\cancel{\textcolor{red}{- 4}}} = 24$

$h = 24$